Structural characterization of short hybrid urea/carbamate (U/C) foldamers: A case of partial helix unwinding. Issue 6 (November 2013) - Nelli, Yella Reddy; Fischer, Lucile; Collie, Gavin W.; Kauffmann, Brice; Guichard, Gilles; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT Aliphatic oligoureas (NHCH(R)CH2NHCO)n and oligocarbamates (NHCH(R)CH2OCO)n are two classes of synthetic peptidomimetic oligomers whose backbone is isosteric to that of γ‐peptides. We have shown recently that the constituent units of these backbones (i.e., amide (A), carbamate (C) and urea (U) units) can be combined in various ways to generate new heterogeneous oligomers with well‐defined secondary structures. For example, oligomers consisting of urea (U) and carbamate (C) linkages arranged in a 1:1 pattern adopt a helical conformation akin to that of urea homoligomers and γ‐peptide foldamers. In this case, helix formation is mainly driven by U units whose propensity for folding surpasses that of C units. Here, we have investigated further the influence of the U/C ratio on the folding preference of such heterogeneous oligomers. We report the synthesis and the structural analysis of a short oligomer with a 2:3 U/C ratio and two consecutive carbamate linkages. X‐ray diffraction analysis reveals a helical structure that unwinds at one end. In contrast, a cognate oligomer prepared for comparison and containing four contiguous urea units adopts a fully helical conformation in the crystalline state. These results which are supported by data in solution indicate that the balance between U and C units should be carefully adjusted and that consecutive C linkages should be avoided for optimal helix formation. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 687–697, 2013.